The Effect of Progestin Source on Some Reproductive Performance in Akkaraman Ewes - Şen, Uğur; Gökçek, Dilek; Bayrak, Büşra (My University, 2022)
This study was conducted to determine the effect of progestin source on some reproductive performance, lamb birth weight and lamb mortality rate in Akkaraman ewes. A total of 40 Akkaraman sheep breed with similar live weights (51.3 ± 1.5 kg) and at least with two parturitions was used as experimental animals. 96 hours prior to estrus synchronization application, intramuscular injection of 1 cc PGF2α was performed to lutalyse the corpus luteum on the ovary in all ewes. The ewes were allocated randomly into two groups according to body weight. Estrus of ewes in the first group (n=20) were synchronized with intra-vaginal CIDR device containing 0.30 g natural progesterone. Estrus of ewes in the second group (n=20) were synchronized with intra-vaginal sponge containing 30 mg flugestone acetate (FGA). CIDR and sponge were withdrawn following 12 days and 600 IU PMSG were injected intramuscularly. After 24 hours from injections, all ewes were introduced to Akkaraman rams and ewes in estrus were recorded. There were no significant differences between natural and synthetic progesterone applications in terms of estrus rate, gestation rate and duration of gestation in Akkaraman ewes. Additionally, lamb birth weight and lamb mortality rates were similar in both experimental groups. However, application of CIDR increased total and multiple lamb birth rates of Akkaraman ewes (P
Keywords: Biyoloji